The transition from hospital to home following acute coronary syndrome: an exploratory qualitative study of patient perceptions and early experiences in two countries. (10th December 2020) - Crawshaw, Jacob; Bartoli-Abdou, John K; Weinman, John; McRobbie, Duncan; Stebbins, Marilyn; Brock, Tina; Auyeung, Vivian
Abstract: Objectives: Following acute coronary syndrome (ACS), it is standard practice for stable patients to be discharged as quickly as possible from hospital. If patients are not adequately supported at this time, issues such as readmission can occur. We report findings from an exploratory qualitative study investigating the perceptions and early experiences of patients transitioning from hospitals in the UK and USA to home following ACS. Methods: Within 1 month of discharge, we conducted semi-structured telephone interviews with patients hospitalised for ACS (UK: n = 8; USA: n = 9). Data were analysed using the Framework Method. Key findings: We identified four superordinate themes. Coping, adjustment and management: Patients were still adjusting to the physical limitations caused by their event but most had begun to implement positive lifestyle changes. Gaps in care transition: Poor communication and organisation postdischarge resulted in delayed follow-up for some patients causing considerable frustration. Quality of care from hospital to home: Patients experienced varied inpatient care quality but had largely positive interactions in primary/community care. Pharmacy input during care transition was viewed favourably in both countries. Medication-taking beliefs and behaviour: Patients reported good initial adherence to treatment but side effects were a concern. Conclusions: ACS patients experienced gaps in care early in the transition from hospital to home. Poor communication and uncoordinated support postdischarge negatively impacted patient experience. Further research is needed to determine how patients' early experiences following ACS can affect longer-term outcomes including healthcare engagement and treatment maintenance.